A novel role for small molecule glycomimetics in the protection against lipid-induced endothelial dysfunction: Involvement of Akt/eNOS and Nrf2/ARE signaling - Mahmoud, Ayman M.; Wilkinson, Fiona L.; Jones, Alan M.; Wilkinson, James A.; Romero, Miguel; Duarte, Juan; Alexander, M. Yvonne (Biochimica et biophysica acta. General subjects, 2017)
Glycomimetics are a diverse array of saccharide-inspired compounds, designed to mimic the bioactive functions of glycosaminoglycans. Therefore, glycomimetics represent a unique source of novel therapies to target aberrant signaling and protein interactions in a wide range of diseases. We investigated the protective effects of four newly synthesized small molecule glycomimetics against lipid-induced endothelial dysfunction, with an emphasis on nitric oxide (NO) and oxidative stress. Four aromatic sugar mimetics were synthesized by the stepwise transformation of 2,5-dihydroxybenzoic acid to derivatives (C1–C4) incorporating sulfate groups to mimic the structure of heparan sulfate. Glycomimetic-treated human umbilical vein endothelial cells (HUVECs) were exposed to palmitic acid to model lipid-induced oxidative stress. Palmitate-induced impairment of NO production was restored by the glycomimetics, through activation of Akt/eNOS signaling. Furthermore, C1-C4 significantly inhibited palmitate-induced reactive oxygen species (ROS) production, lipid peroxidation, and activity and expression of NADPH oxidase. These effects were attributed to activation of the Nrf2/ARE pathway and downstream activation of cellular antioxidant and cytoprotective proteins. In ex vivo vascular reactivity studies, the glycomimetics (C1–C4) also demonstrated a significant improvement in endothelium-dependent relaxation and decreased ROS production and NADPH oxidase activity in isolated mouse thoracic aortic rings exposed to palmitate. The small molecule glycomimetics, C1–C4, protect against lipid-induced endothelial dysfunction through up-regulation of Akt/eNOS and Nrf2/ARE signaling pathways. Thus, carbohydrate-derived therapeutics are a new class of glycomimetic drugs targeting endothelial dysfunction, regarded as the first line of defense against vascular complications in cardiovascular disease. [Display omitted] •Small molecule glycomimetics protect against endothelial dysfunction.•Glycomimetics up-regulate Akt/eNOS signaling and restore nitric oxide bioavailability.•Glycomimetics reduce oxidative stress via activation of Nrf2/ARE signaling.•Glycomimetics improve endothelium-dependent relaxation and decrease ROS production and NADPH oxidase activity.